Study on the Biological Characteristics of CD133+ Cells Interfered by RNA Interference in Gastric Cancer. (19th March 2014) - Yu, Ji-wei; Wang, Shou-lian; Wu, Ju-gang; Lu, Rui-qi; Ni, Xiao-chun; Cai, Cheng; Jiang, Bo-jian
Abstract : Background . To detect the changes of biological characteristics in gastric cancer cells interfered by CD133-specific small interfering RNA (siRNA). Methods . First to select the siRNA which has the strongest interference effect among 3 siRNAs (i.e., siRNA1, siRNA2, and siRNA3) in KATO-III cells by RT-PCR and Western blotting assays. Then, CD133 + cells were sorted out from KATO-III cells using an immunomagnetic bead sorting method and transfected with the selected siRNA. Furthermore, the proliferating characteristics, the antichemotherapeutic assessment, Transwell invasion assay, monoclonal sphere formation assay, and subcutaneous transplanted tumor formation assay in nude mice were investigated. Results . siRNA3 showed the strongest interference effect in KATO-III cells. As compared to the uninterfered control group, the CD133 + cells treated by siRNA3 showed significant decreases in the abilities of proliferation, invasion, clone sphere formation, and resistance to antitumour drugs as well as the weight and size of the transplanted tumor, which was nearly similar to that of CD133 − cells. Additionally, the protein expression level of the EMT factor E-cadherin increased while those of EMT-related Snail and N-cadherin decreased in CD133 + cells interfered by siRNA3. Conclusion . Inhibition of CD133 gene expression reduces the abilities of gastric cancer cells in proliferation, invasion, clonal sphere formation, and chemoresistance as well as tumor formation in nude mice.